A quantitative study on the policies for cultivated land abandonment governance in China based on the framework of “tool-target-effectiveness” - CHEN Mengmeng, HAN Qing (Ziyuan Kexue)
[Objective] In this study, a quantitative evaluation of cultivated land abandonment governance policies was carried out to provide a basis for guaranteeing the effective operation of cultivated land abandonment governance policy. [Methods] Using the content analysis method and policy modeling consistency (PMC) index, we constructed a policy tool-target-effectiveness analysis framework to quantify and evaluate the cultivated land abandonment governance policy of the central government, main grain-producing areas, and non-main grain-producing areas of China. [Results] The study found that: (1) Cultivated land abandonment governance policies were temporally phased, spatially continuous, and the use of policy tools was becoming increasingly diversified. (2) The policy tools of the three policy subjects were generally based on information disclosure and guidance on measures, each with its own focus. While the administrative control policies were more frequently used by the central government, the main grain-producing areas focused on the assessment and accountability and indirect guidance, and the non-main grain-producing areas preferred the assessment and accountability and the establishment of information ledgers. (3) In terms of policy targets, the three policy subjects attached great importance to strictly controlling the quantity of abandoned land, but still need to pay more attention to improving the quality of cultivated land and optimizing the allocation of agricultural production factors. (4) In terms of policy effectiveness, compared with the progressive development period, China’s cultivated land abandonment governance policy was more reasonably designed in the comprehensive management period, and the effectiveness of the policies shows: central government > non-grain-producing areas > grain-producing areas. But policy areas and policy focus still have space for improvements. [Conclusion] In the future, the three policy subjects should use a combination of policy tools, formulate more targeted and operable cultivated land abandonment governance policies, construct a diversified target system for cultivated land abandonment governance policies, promote cultivated land abandonment governance by types and levels, gradually improve the content effectiveness of cultivated land abandonment governance policies, and give full play to the incremental effect of the policies on the governance of cultivated land abandonment.